Adaptation to soil type contributes little to local adaptation in an Italian and a Swedish ecotype of Arabidopsis thaliana on contrasting soils - Ellis, Thomas James; Ågren, Jon (Biology letters (2005), 2024)
Natural populations are subject to selection caused by a range of biotic and abiotic factors in their native habitats. Identifying these agents of selection and quantifying their effects is key to understanding how populations adapt to local conditions. We performed a factorial reciprocal-transplant experiment using locally adapted ecotypes of Arabidopsis thaliana at their native sites to distinguish the contributions of adaptation to soil type and climate. Overall adaptive differentiation was strong at both sites. However, we found only very small differences in the strength of selection on local and non-local soil, and adaptation to soil type at most constituted only a few per cent of overall adaptive differentiation. These results indicate that local climatic conditions rather than soil type are the primary driver of adaptive differentiation between these ecotypes.